SMO mutations confer poor prognosis in malignant pleural mesothelioma - Signorelli, Diego (Transl Lung Cancer Res, 2020)
BACKGROUND: Malignant pleural mesothelioma (MPM) is an aggressive tumor but approximately 12% of patients survive more than 3 years. The biological differences underlying better outcomes are not known. Several targeted agents and immunotherapy have been ineffective. Hedgehog (Hh) is one emerging pathway. We compared the biological profiles of patients with different survival, investigating the most frequently altered genes, including the Hh pathway. METHODS: We analyzed 56 MPM. A 36-month overall survival (OS) cut-off divided patients into 32 normo (NS) and 24 long (LS) survivors. We used next generation sequencing to test 21 genes, immunohistochemistry to evaluate SMO expression. Mutation differences between NS and LS and their associations with clinical features were analysed by Fisher’s test, OS with the Kaplan-Meier method and its association with mutations by univariate and multivariate Cox proportional hazard models. RESULTS: Clinical features were similar in both groups. Eighteen out of 56 patients (32%) were wild-type for the genes analysed. At least five had mutations in BAP1, NF2, TP53, SMO and PTCH1 with no significant differences between the groups except for SMO. SMO, a member of the Hh pathway, was mutated only in NS (15.6%) and only SMO mutations were significantly associated with poor prognosis at univariate (HR =4.36, 95% CI: 2.32–8.18, P<0.0001) and multivariate (HR =9.2, 95% CI: 3.0–28.4, P=0.0001) analysis. All SMO mutated patients expressed high protein levels. CONCLUSIONS: SMO mutations were clearly associated with worse prognosis. SMO may be a therapeutic target but this needs to be confirmed in a prospective trial.